Academic Games in Validation Events: A Study of Academic Roles and Practices - Khanna, Rebecca; Savin-Baden, Maggi (Critical Studies in Teaching and Learning, 2023)
This paper presents the results of a three-year study that examined academicsâ€™ espoused and actual practices in validation or approval events of UK degree courses. The study used narrative inquiry to explore academics’ accounts. The paper provides a literature review and then presents the findings which indicate that often procedural processes interrupt the process of curriculum making. The paper uses scenarios to illustrate the ways in which procedural processes can result in subverting and subversive practices during the validation process. It is, therefore, argued that academics take up particular stances, defined here as positional identities, which may help or hinder the validation process. The paper argues that by ignoring staff experiences, the risk is that dominant discourses of regulation become accepted without question and the spaces available for dialogue about professional futures, alongside creation of flexible curricula to address these needs, are crowded out by the performative requirements of the process